Optimization of Lyophilization Modes for Culture Medium Used in Mycobacterial Cultivation - Zavhorodniy, Andriy; Bilushko, Viktor; Pozmohova, Svitlana; Paliy, Anatoliy; Kalashnyk, Mykola; Pavlichenko, Olena; Sviridova, Karina; Tischenko, Oleksandra (Problems of Cryobiology and Cryomedicine, 2025)
The paper presents the results of improving the lyophilization mode of egg-based culture medium for mycobacterial cultivation. The freezing of culture medium of 200 cm3 volume at -30°C was established to provide more optimal conditions for lyophilization than other options we suggested here (200 cm3 at –20°C and 300 cm3 at –20 and –30°C). This enables to reduce the number of rejected vials and preserve the elective properties of the medium. Other freezing modes occurred to be less efficient. Our findings also showed the use of recommended modes for lyophilization as capable to accelerate the appearance of first signs of mycobacterial growth by 1–2 days. Probl Cryobiol Cryomed 2024; 34(4):261–267